2017
DOI: 10.3171/2017.7.focus17321
|View full text |Cite
|
Sign up to set email alerts
|

The impact of curve severity on obstetric complications and regional anesthesia utilization in pregnant patients with adolescent idiopathic scoliosis: a preliminary analysis

Abstract: OBJECTIVEAdolescent idiopathic scoliosis (AIS), the most common type of scoliosis, often presents immediately prior to a woman’s childbearing years; however, research investigating the impact of AIS on women’s health, particularly pregnancy delivery outcomes, is sparse, with existing literature reporting mixed findings. Similarly limited are studies examining the change in scoliotic curve during or after pregnancy. Therefore, this study aims to determine 1) the impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 20 publications
0
14
0
1
Order By: Relevance
“…46 - 54 Only six studies were prospective (12%). 10 , 55 - 59 Most were North American (40%) 6 , 10 , 12 , 16 , 17 , 19 , 22 , 23 , 25 , 26 , 35 , 38 , 41 , 42 , 45 , 46 , 49 , 52 , 55 , 57 or European (44%) studies. 11 , 14 , 15 , 20 , 21 , 24 , 28 - 34 , 37 , 44 , 47 , 50 , 51 , 53 , 56 , 58 , 59 The study population of all included publications was recruited from hospitals or medical centres, except for two studies, where participants were recruited from the Gothenburg Scoliosis Database.…”
Section: Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…46 - 54 Only six studies were prospective (12%). 10 , 55 - 59 Most were North American (40%) 6 , 10 , 12 , 16 , 17 , 19 , 22 , 23 , 25 , 26 , 35 , 38 , 41 , 42 , 45 , 46 , 49 , 52 , 55 , 57 or European (44%) studies. 11 , 14 , 15 , 20 , 21 , 24 , 28 - 34 , 37 , 44 , 47 , 50 , 51 , 53 , 56 , 58 , 59 The study population of all included publications was recruited from hospitals or medical centres, except for two studies, where participants were recruited from the Gothenburg Scoliosis Database.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…While more than half of the studies were published prior to 2010 (N.=30), 10 - 12 , 14 , 16 , 17 , 20 - 23 , 25 , 28 , 31 , 33 , 34 , 36 - 38 , 45 - 49 , 51 - 54 , 56 - 58 some were published in the last decade (2011-2023) (N.=20) 6 , 15 , 18 , 19 , 24 , 26 , 27 , 29 , 30 , 32 , 35 , 39 , 41 - 44 , 50 , 55 , 59 , 60 including 14 published post-2015. 6 , 15 , 18 , 19 , 26 , 27 , 32 , 35 , 39 , 41 - 44 , 59 The mean age of participants was difficult to estimate as some studies provided the mean age of the entire population, which included both male and female participants. In contrast, others reported the mean age at the end of the scoliosis treatment, whether conservative or surgical.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Среди более поздних работ внимания заслуживают исследования, опубликованные в 2017 г. Chan et al [14], а также Dewan et al [15]. В первое исследование вошли данные о 51 пациентке со сколиозом меньших степеней, чем IV: средний угол деформации при операции -25°, медианный -31°.…”
Section: таблицаunclassified
“…[10][11][12][13][14][15][16] Similarly, IS has been associated with lower rates of perinatal neuraxial anesthesia use in some studies, 2,14,15,17 with other studies showing no significant influence of IS on regional anesthesia decision making or success of the epidural placement. 18,19 These prior studies were relatively small, with fewer than 300 subjects in total, except for one meta-analysis of these small studies. 20 Given the conflicting results, there is a need for investigation into the delivery experiences of females with scoliosis in a large, diverse population with data stratification based on physical characteristics and demographic factors.…”
mentioning
confidence: 99%
“…Although some studies have suggested that females with a history of IS have higher rates of CSs,7–9 other studies have disputed these results 10–16. Similarly, IS has been associated with lower rates of perinatal neuraxial anesthesia use in some studies,2,14,15,17 with other studies showing no significant influence of IS on regional anesthesia decision making or success of the epidural placement 18,19. These prior studies were relatively small, with fewer than 300 subjects in total, except for one meta-analysis of these small studies 20.…”
mentioning
confidence: 99%